A single positively selected West Nile viral mutation confers increased virogenesis in American crows - Brault, Aaron C; Huang, Claire Y-H; Langevin, Stanley A; Kinney, Richard M; Bowen, Richard A; Ramey, Wanichaya N; Panella, Nicholas A; Holmes, Edward C; Powers, Ann M; Miller, Barry R (Nature genetics, 2007)
West Nile virus (WNV), first recognized in North America in 1999, has been responsible for the largest arboviral epiornitic and epidemic of human encephalitis in recorded history. Despite the well-described epidemiological patterns of WNV in North America, the basis for the emergence of WNV-associated avian pathology, particularly in the American crow (AMCR) sentinel species, and the large scale of the North American epidemic and epiornitic is uncertain. We report here that the introduction of a T249P amino acid substitution in the NS3 helicase (found in North American WNV) in a low-virulence strain was sufficient to generate a phenotype highly virulent to AMCRs. Furthermore, comparative sequence analyses of full-length WNV genomes demonstrated that the same site (NS3-249) was subject to adaptive evolution. These phenotypic and evolutionary results provide compelling evidence for the positive selection of a mutation encoding increased viremia potential and virulence in the AMCR sentinel bird species.